EVALUATION AND OPTIMIZATION OF SUCKER ROD PUMP IN WELL X AGAINST HYDROCARBON FLUID PRODUCTION INCREASE Y FIELD - KRISTOFOL WAAS; BERTHY PELASULA; MELADY LOKOLLO (CV KULTURA DIGITAL MEDIA, 2023)
To increase the productivity of a sucker rod pump, it is necessary to pay attention to the pump production capacity, stroke length, pumping speed. The decline in pump production can be caused by various factors. Well X experienced a decrease in production, this was due to not meeting the optimum target that could be achieved by the pump, where at the time the research was carried out, well X had already been produced using a Sucker Rod Pump (SRP). This is a method of artificial lifting (Artificial Lift) that is most commonly used, due to the combined motion between the equipment that is on the surface and the equipment that is below the surface. The Sucker Rod Pump (SRP) Artificial Lift method is used in several wells in the KLAMONO – PERTAMINA EP CEPU Papua Field. To increase the production of well X, it is necessary to take optimization measures by increasing the initial SPM parameters. Before this optimization is carried out, the pump needs to be evaluated first to be able to find out the pump capacity by finding the PI and Qmax values to make the IPR curve. PI and Qmax in the X well studied by PI is 12.326 and Qmax is 1539.66 bfpd, The results obtained using the vogel method using the Pipesim application (PIP) for well X are only capable of producing 315 bfpd at 18 SPM with a Pwf of 187.279 psi and can still be optimized by increasing the Strokes Per Minute Parameter (SPM) to 24 SPM by production yield increased by 891 bfpd at a Pwf pressure of 129,847 psi.